1985
DOI: 10.1073/pnas.82.23.8227
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia-induced teratogenesis is mediated by a functional deficiency of arachidonic acid.

Abstract: Congenital malformations now represent the largest single cause of mortality in the infant of the diabetic mother. The mechanism by which diabetes exerts its teratogenic effects is not known. This study evaluated whether arachidonic acid might be involved, a possibility raised by the role of arachidonic acid in palatal elevation and fusion, processes analogous to neural tube folding and fusion. This hypothesis was tested in two animal models of diabetic embryopathy, the in vivo pregnant diabetic rat and the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
97
0
5

Year Published

1991
1991
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(110 citation statements)
references
References 37 publications
8
97
0
5
Order By: Relevance
“…The major products of lipid peroxidation, the hydroperoxides, are known stimulants of prostaglandin biosynthesis but inhibit the production of prostacyclin [54], an imbalance which may have deleterious effects on the embryo. The previous findings of a beneficial effect of arachidonic acid [33,34], prostaglandin E~ and F2c~ and prostacyclin [39] on embryos in a diabetic environment may also relate to this notion, since the supplementation of these substances may correct a possible imbalance in prostaglandin biosynthesis. Likewise, the finding of a beneficial effect of myo-inositol supplementation to high-glucose culture [39,40], compensating for a decreased embryonic uptake of this hexose [41], may be explained by a restored production of phosphatidylinositol and a subsequent normalization of phospholipase A2 activity [55].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The major products of lipid peroxidation, the hydroperoxides, are known stimulants of prostaglandin biosynthesis but inhibit the production of prostacyclin [54], an imbalance which may have deleterious effects on the embryo. The previous findings of a beneficial effect of arachidonic acid [33,34], prostaglandin E~ and F2c~ and prostacyclin [39] on embryos in a diabetic environment may also relate to this notion, since the supplementation of these substances may correct a possible imbalance in prostaglandin biosynthesis. Likewise, the finding of a beneficial effect of myo-inositol supplementation to high-glucose culture [39,40], compensating for a decreased embryonic uptake of this hexose [41], may be explained by a restored production of phosphatidylinositol and a subsequent normalization of phospholipase A2 activity [55].…”
Section: Discussionmentioning
confidence: 90%
“…Thus, both a high concentration of glucose [9], a low glucose concentration [31] and a high concentration of [3-hydroxybutyrate [32] have been shown to be teratogenic in vitro. Furthermore, various consequences of increased ambient glucose concentration have been suggested to play a role in the disturbed embryogenesis, such as arachidonic acid depletion [33,34], hyperaccumulation of sorbitol [35][36][37][38], deficiency of myo-inositol [36,37,[39][40][41] or alterations in trace metal concentrations of the offspring [42,43]. Mannose [44,45] and somatomedin inhibitors from serum of diabetic rats [46] also cause embryonic malformations.…”
Section: Discussionmentioning
confidence: 99%
“…Although several teratogenic factors such as sorbitol accumulation [51], myo-inositol deficiency [19], arachidonic acid deficiency [18], altered prostaglandin metabolism [52] and increased concentration of 3-deoxyglucosone [53] are altered in embryos of diabetic pregnancy, the mechanisms by which these abnormalities lead to dysmorphogenesis have not been determined. Only recently, it has been shown that oxidative stress induced by maternal diabetes could lead to neural tube defects by impairing the expression of genes that control developmental processes [23].…”
Section: Discussionmentioning
confidence: 99%
“…abolic abnormalities including increased superoxide dismutase activity [15,16,17], reduced concentrations of myoinositol and arachidonic acid [18,19] and inhibition of the pentose phosphate shunt pathway [20]. Moreover, the frequency of embryonic malformations in diabetic pregnancy has been reported to be reduced by dietary supplements of antioxidants such as vitamin E or vitamin C [16,21,22,23] and butylated hydroxytoluene [24], suggesting that oxidative stress is involved in embryonic dysmorphogenesis.…”
mentioning
confidence: 99%
“…Preventive strategies have been examined in laboratory animals based on knowledge of these pathways, in attempts to reduce diabetic embryopathy associated with high glucose levels. For example, birth defect incidence has been reduced in diabetic mice by dietary supplementation with myoinositol (Baker et al, 1990), arachidonic acid (Goldman et al, 1985;Pinter et al, 1986), lipoic acid (Wiznitzer et al, 1999), or antioxidants including vitamin E (Sivan et al, 1996) and vitamin C (Siman and Eriksson, 1997). Torchinsky et al (1997) stimulated uterine immune cells in pregnant mice in an attempt to reduce fetal resorptions associated with diabetes, and made the unexpected observation of significantly reduced malformed fetuses.…”
Section: Maxillary Lengthmentioning
confidence: 99%